Patiromer Controls RAASi-Associated HK in Patients with Diabetes and CKD - Lederman, Lynne (MD Conference Express, 2015)
Renin-angiotensin-aldosterone system inhibitors (RAASis) are beneficial and recommended for patients with chronic kidney disease (CKD) and type 2 diabetes mellitus (T2DM). However, hyperkalemia (HK) often limits RAASi therapy. The OPAL-HK [NCT01810939] trial found that patiromer normalized serum potassium (s-K+) and prevent HK recurrence compared with placebo. This article discusses a poster investigating the prespecified analysis of the subgroup with T2DM in OPAL-HK.